Clinical recommendations for postoperative care after heart transplantation in children: 21 years of a single-center experience (Clinics, 2014)
Heart transplantation is an option for children with complex congenital heart disease and cardiomyopathies. A patient's quality of life and long-term survival depend on successful management of the surgical complications and adverse side effects of immunosuppression. The purpose of this review was to summarize the practical management of postoperative care in this patient population and to make recommendations for the future.